1996
DOI: 10.1021/bi951833i
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Binding Causes Movement in the ATP Binding Domain of Escherichia coli Adenylate Kinase

Abstract: Crystallographic evidence suggests that there is a large hinged domain motion associated with substrate binding in adenylate kinase. To test this hypothesis, resonance energy transfer measurements of substrate binding were initiated. Adenylate kinase from Escherichia coli consists of three domains: the main body of the enzyme with alpha-helical and beta-sheet secondary structure, and domains that close over the AMP and ATP binding sites. Four single tryptophan mutants were constructed to map distances. Two try… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 24 publications
1
29
1
Order By: Relevance
“…2b, demonstrates that the lid domain of AK is in dynamical equilibrium between the open and closed conformational modes with each mode containing an ensemble of substates. Our results are in sharp contrast to the common view that AK's lid should remain open in the absence of substrates (13,(15)(16)(17), whereas binding would cause a global conformational change resulting in lid closure. That the substrate-free enzyme should remain in the open form has also been assumed (a reasonable supposition given the existing ensemble-averaged results) in the analysis of NMR relaxationdispersion experiments performed on AK (19).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…2b, demonstrates that the lid domain of AK is in dynamical equilibrium between the open and closed conformational modes with each mode containing an ensemble of substates. Our results are in sharp contrast to the common view that AK's lid should remain open in the absence of substrates (13,(15)(16)(17), whereas binding would cause a global conformational change resulting in lid closure. That the substrate-free enzyme should remain in the open form has also been assumed (a reasonable supposition given the existing ensemble-averaged results) in the analysis of NMR relaxationdispersion experiments performed on AK (19).…”
Section: Resultscontrasting
confidence: 99%
“…AK was chosen for this study because many aspects of this enzyme have been studied both experimentally (11)(12)(13)(14)(15)(16)(17)(18)(19) and theoretically (20)(21)(22)(23)(24). It is an ubiquitous enzyme that helps maintain the energy balance in cells by catalyzing the reversible reaction, Mg 2ϩ ⅐ATP ϩ AMP º Mg 2ϩ ⅐ADP ϩ ADP.…”
mentioning
confidence: 99%
“…Although the reactivity of rabbit muscle AK is slightly inhibited at higher AMP concentrations (29, 32), E. coli AK exhibits its maximum turnover rate around 0.2 mM AMP followed by a steep drop, which plateaus at still higher AMP concentrations (33)(34)(35). This observation has been traditionally attributed to greater substrate inhibition by AMP in E. coli AK compared with the rabbit isoform; yet, the issue of whether the reaction involves competitive or non-competitive inhibition by AMP at the ATP binding site remains unresolved (15,33,(35)(36)(37).Here, we report a comprehensive kinetic study of the forward reaction of AK, exploring concentrations of nucleotides and Mg 2ϩ that are comparable to those inside E. coli cells, [Mg 2ϩ ] ϳ 1-2 mM (38) and [ATP] up to 3 mM (39). We discovered a previously unreported phenomenon: an increase in the forward reaction rate of AK with increasing Mg 2ϩ concentrations, where the stoichiometry of Mg 2ϩ to the enzyme is greater than one.…”
mentioning
confidence: 99%
“…Although the reactivity of rabbit muscle AK is slightly inhibited at higher AMP concentrations (29,32), E. coli AK exhibits its maximum turnover rate around 0.2 mM AMP followed by a steep drop, which plateaus at still higher AMP concentrations (33)(34)(35). This observation has been traditionally attributed to greater substrate inhibition by AMP in E. coli AK compared with the rabbit isoform; yet, the issue of whether the reaction involves competitive or non-competitive inhibition by AMP at the ATP binding site remains unresolved (15,33,(35)(36)(37).…”
mentioning
confidence: 99%
“…The enzyme contains two distinct nucleotide binding sites: the MgATP site, which binds MgATP and MgADP, and the AMP site, which is specific for AMP and uncomplexed ADP. The substrate-induced conformation changes in AK have been the subject of a number of investigations (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Based on the comparison of AK crystal structures representing the enzyme in different ligand forms, apo-form (from pig muscle), enzyme-AMP binary complex (from beef heart mitochondrial matrix), and enzyme-AP 5 A complex (from Escherichia coli), Schulz and co-workers (15,18) suggested that AK undergoes large structural changes upon substrates binding.…”
mentioning
confidence: 99%